Evaluation of Alternative Killing Agents for Aedes aegypti (Diptera: Culicidae) in the Gravid Aedes Trap (GAT). Issue 4 (31st May 2016) - Heringer, Laila; Johnson, Brian J.; Fikrig, Kara; Oliveira, Bruna A.; Silva, Richard D.; Townsend, Michael; Barrera, Roberto; Eiras, Álvaro E.; Ritchie, Scott A.
Abstract: The Gravid Aedes Trap (GAT) uses visual and olfactory cues to attract gravid Aedes aegypti (L.) that are then captured when knocked down by a residual pyrethroid surface spray. However, the use of surface sprays can be compromised by poor availability of the spray and pesticide resistance in the target mosquito. We investigated several "alternative" insecticide and insecticide-free killing agents for use in the GAT. This included long-lasting insecticide-impregnated nets (LLINs), vapor-active synthetic pyrethroids (metofluthrin), canola oil, and two types of dry adhesive sticky card. During bench top assays LLINs, metofluthrin, and dry sticky cards had 24-h knockdown (KD) percentages >80% (91.2 ± 7.2%, 84.2 ± 6.8%, and 83.4 ± 6.1%, respectively), whereas the 24-h KD for canola oil was 70 ± 7.7%, which improved to 90.0 ± 3.7% over 48 h. Importantly, there were no significant differences in the number of Ae. aegypti collected per week or the number of traps positive for Ae. aegypti between the sticky card and canola oil treatments compared with the surface spray and LLIN treatments in semifield and field trials. These results demonstrate that the use of inexpensive and widely available insecticide-free agents such as those described in this study are effective alternatives to pyrethroids in regions with insecticide-resistant populations. The use of such environmentally friendly insecticide-free alternatives will also be attractive in areas where there is substantial resistance to insecticide use due to environmental and public health concerns.